Influence of thermal and mechanical cycling on the flexural strength of ceramics with titanium or gold alloy frameworks - Oyafuso, Denise Kanashiro [UNESP]; Özcan, Mutlu; Bottino, Marco Antonio [UNESP]; Itinoche, Marcos Koiti [UNESP] (Elsevier, 2008)
Objectives: The aim of this study was to evaluate the effect of thermal and mechanical cycling alone or in combination, on the flexural strength of ceramic and metallic frameworks cast in gold alloy or titanium. Methods: Metallic frameworks (25 mm × 3 mm × 0.5 mm) (N = 96) cast in gold alloy or commercial pure titanium (Ti cp) were obtained using acrylic templates. They were airborne particle-abraded with 150 μm aluminum oxide at the central area of the frameworks (8 mm × 3 mm). Bonding agent and opaque were applied on the particle-abraded surfaces and the corresponding ceramic for each metal was fired onto them. The thickness of the ceramic layer was standardized by positioning the frameworks in a metallic template (height: 1 mm). The specimens from each ceramic-metal combination (N = 96, n = 12 per group) were randomly assigned into four experimental fatigue conditions, namely water storage at 37 °C for 24 h (control group), thermal cycling (3000 cycles, between 4 and 55 °C, dwell time: 10 s), mechanical cycling (20,000 cycles under 10 N load, immersion in distilled water at 37 °C) and, thermal and mechanical cycling. A flexural strength test was performed in a universal testing machine (crosshead speed: 1.5 mm/min). Data were statistically analyzed using two-way ANOVA and Tukey's test (α = 0.05). Results: The mean flexural strength values for the ceramic-gold alloy combination (55 ± 7.2 MPa) were significantly higher than those of the ceramic-Ti cp combination (32 ± 6.7 MPa) regardless of the fatigue conditions performed (p < 0.05). Mechanical and thermo-mechanical fatigue decreased the flexural strength results significantly for both ceramic-gold alloy (52 ± 6.6 and 53 ± 5.6 MPa, respectively) and ceramic-Ti cp combinations (29 ± 6.8 and 29 ± 6.8 MPa, respectively) compared to the control group (58 ± 7.8 and 39 ± 5.1 MPa, for gold and Ti cp, respectively) (p < 0.05) (Tukey's test). While ceramic-Ti cp combinations failed adhesively at the metal-opaque interface, gold alloy frameworks exhibited a residue of ceramic material on the surface in all experimental groups. Significance: Mechanical and thermo-mechanical fatigue conditions decreased the flexural strength values for both ceramic-gold alloy and ceramic-Ti cp combinations with the results being significantly lower for the latter in all experimental conditions. © 2007 Academy of Dental Materials.
Keywords: Ceramic; Flexural strength; Gold; Mechanical cycling; Thermal cycling; Titanium; Bending strength; Gold alloys; Mechanical testing; Thickness measurement; Titanium alloys; Ceramic metal alloys; Metallic frameworks; Ceramic materials; alloy; gold alloy; titanium; water; analysis of variance; comparative study; dental care; denture; heat; materials testing; pliability; Analysis of Variance; Dental Casting Technique; Dental Stress Analysis; Denture Design; Denture, Partial, Fixed; Gold Alloys; Heat; Materials Testing; Metal Ceramic Alloys; Pliability; Water